Neurodevelopmental Outcome at 2 Years for Preterm Children Born at 22 to 34 Weeks' Gestation in France in 2011: EPIPAGE-2 Cohort Study. Issue 1 (March 2018) - Pierrat, V.; Marchand-Martin, L.; Arnaud, C.; Kaminski, M.; Resche-Rigon, M.; Lebeaux, C.; Bodeau-Livinec, F.; Morgan, A.S.; Goffinet, F.; Marret, S.; Ancel, P.Y.
Abstract : ( BMJ . 2017;358:j3448) Although survival of preterm babies has increased worldwide along with a decrease in severe neonatal morbidity, the risk of neurodevelopmental and behavioral disabilities continues to be high in these children. In fact, developmental delay has replaced survival as the major concern for children born preterm. Early identification of risk factors for neurodevelopmental delay could lead to improved access to formal evaluation and subsequent intervention, potentially resulting in better long-term outcomes for the children. The EPIPAGE-2 study is a population-based cohort study from France that is evaluating infants born between 22 and 34 weeks gestation. Previously published reports from the EPIPAGE study have analyzed survival data as well as severe neonatal morbidity over a 15-year time period. In the current study, the cohort was analyzed to determine neuromotor, sensory, and neurodevelopmental outcomes at 2 years corrected age for children born alive from 22 to 34 weeks' gestation. Children from the cohort enrolled in 2011 were compared with the cohort from 1997.